Dampak Goal Setting Terhadap Individual Personal Development Alumni Seminar Internasional Haggai Institute yang Berasal dari Indonesia pada Periode Tahun 2000-2002 - Tarigan, Nuah Perdamenta (Bina Nusantara University, 2011)
According to anthropologist, religion has a close relationship to one nation?s culture. Haggai Institute saw the same perspective of management principles, and more about leadership, where it believes that any organization needs to change paradigm from its comfort zone that mostly everywhere. The research is hoped to be useful in the importance of designing the life purpose in every active Christian leader in building the future of service, family, community, and work. The research result towards alumni of year 2000-2002 of Haggai Institute International Seminar which will significant enough in identify the existence and development that they havedone after joining the Haggai Seminar, especially in designing life purpose individually. Afterward effects from the seminar to graduates year 2000-2002 is well. The alumni seem to have kept and applied Designing Purpose of Life in their own life.